MATHEMATICAL MODEL FOR DETERMINATION OF CONTACT RESISTANCE IN PLACE OF WIRE BREAKAGE OF OVER-HEAD TRANSMISSION LINES - Lezhniuk, Petro; Kutina, Marina (Scientific Works of Vinnytsia National Technical University, 2015)
The paper contains the analysis of factors, influencing the value of contact resistance in the place of over-head transmission line wire fall on the ground. Mathematical model intended for determination of contact resistance in the place of wire fall on the ground is suggested.